Thermal analysis and entropy generation of pulsating heat pipes using nanofluids. (25th June 2016) - Jafarmadar, Samad; Azizinia, Nazli; Razmara, Nayyer; Mobadersani, Farrokh
Highlights: Performance of PHP containing 0.5% Al2 O3, CuO and silver nanofluids is reported. The rate of entropy generation of PHP is investigated for different nanofluids. The effects of particle volume concentration on the entropy generation of PHP are studied. The appropriate volume concentration for the best thermal efficiency is 0.5–1%. Al2 O3 and CuO nanofluids show approximately same rate of entropy generation. Abstract: Demanding of high-performance cooling systems is one of the most challenging and virtual issues in the industry and pulsating heat pipes (PHPs) are effective solutions for this concern. Nanofluids also have attracted attentions, due to its superior heat transfer properties in recent years. In the present study, the flow, heat transfer and entropy generation based on the second law of thermodynamics have been investigated and compared with the flow of Al2 O3, CuO, Ag nanofluid and pure water through PHPs. The results show that, silver nanofluid provides the highest entropy generation. Also, the effects of different particle volume concentrations on the heat and flow characteristics of Al2 O3 nanofluid have been studied. It is indicated that the optimal volume concentration of nanoparticles is about 0.5–1% to minimize the entropy generation and appropriate thermal operation.